Factors Contributing to Uptake of Skilled Delivery in Ada-Foah Subdistrict in the Greater Accra Region - Imurana, H. (University of Ghana, 2019)
Background: Uptake of skilled delivery is identified to be the best pointer of advancement concerning decreasing maternal mortality globally. Also 50% or more pregnant women deliver yearly without a skilled birth attendant worldwide .Maternal mortality Ratio (MMR) in Ghana is currently 319 per 100,000 live births. Majority of the women in the Ada-Foah sub-district do not utilize skilled delivery services according to the District Health Information Management System figures. Maternal Mortality Ratio (MMR) of 70 per 100.000 live births or less by 2030, was the target set by the Sustainable Development Goal which Ghana is working to achieve due to the high maternal mortality ratio in the country. Therefore, assessing the factors contributing to uptake of skilled delivery in Ada- Foah sub district was the purpose of the study. Method: A cross sectional survey was carried out in 10 Child Welfare Clinics (CWC) in the Ada-Foah sub-district with a sample size of 295 mothers with babies born between January and December of the previous year. The data was collected using structured questionnaires. Descriptive statistics such as frequency and percentage distribution were used to describe the socio-demographic characteristics of respondents. Bar chart was used to describe multiple selection questions from the study participants. Pie chart was also used to describe the uptake of skilled delivery chi-square and binary logistic regression analyses (inferential statistical analyses) were used to assess the factors contributing to uptake of skilled delivery. 0.05 level of significant was set. Results: The results of the study indicated that uptake of skilled delivery was high (80%). Factors such as marital status, partner’s level of education and employments status of study participants, cost, and means of transport, staff attitude, previous ANC attendance and affordability of services were the factors that showed significant association with uptake of skilled delivery. Persons who make health and pregnancy related decision did not show significant association with uptake of skilled delivery Conclusion: Numerous factors such as socio-demographic characteristics, cultural perceptions, accessibility to health facility and quality of care influence uptake of skilled delivery. Therefore adequate measures should be put in place by the district health directorate, chiefs, NGO’s and opinion leaders to improve on the uptake of skilled delivery in the sub-district and the district as a whole.
MPH.
Keywords: Maternal Mortality; Greater Accra Region; Skilled Delivery; Quality of Care; Ada-Foah Subdistrict